Factors Delaying Antenatal Management Leading to Maternal Morbidity: Empirical Evidence from Tertiary Care Hospital KPK: Antenatal Management Leading to Maternal Morbidity - Safdar, Sabah; Inayat, Zoopash; Safdar, Sheema (Pakistan BioMedical Journal, 2025)
Antenatal care is a branch of preventive medicine focused on the early detection and prevention of pregnancy disorders. Objective: To determine the frequency of factors responsible for delaying antenatal management leading to maternal morbidity. Methods: This cross-sectional was conducted at Khyber Teaching Hospital. In this study, a total of 151 patients were observed. Before data collection, approval was obtained from the hospital’s ethical committee after approval of the synopsis. All the admitted patients (pregnant women) presented to labor room in Khyber Teaching Hospital meeting the inclusion criteria were recruited for the study explaining the objective of the study to every patient. Inform consent was obtained from the patients. Patients were thoroughly examined according to the routine health assessment protocol of the hospital. Data were collected with the help of a Performa attached. Results: The mean age was 30 ± 12.45 years. 67% of patients were from rural areas while 50 (33%) patients were from urban areas. 65 (43%) patients were un-educated, 53 (35%) patients had primary to secondary education and 33 (22%) patients had an education level above secondary. There was a significant association (p-value=0.001) between the distance from the hospital and delays in antenatal care. Conclusions: It was concluded that antenatal care is essential for reducing maternal and fetal mortality, particularly in developing regions where the maternal mortality ratio remains significantly high. This study identifies key barriers to Antenatal care utilization in Pakistan, such as low education levels, poor socioeconomic status, geographical inaccessibility, and systemic healthcare issues.